Application of additive manufacturing TaBw01 porous tantalum rod in ARCO stage II osteonecrosis of the femoral head - Jingjie Huang; Yifan Jiang; Yang Peng; Lina Hao; Ran Xiong; Tiao Su; Guangxing Chen (Journal of Orthopaedic Surgery and Research)
Abstract Purpose This study aims to investigate the suitable surgical strategies for applying TaBw01 porous tantalum rod across different stages of osteonecrosis of the femoral head (ONFH). Methods TaBw01 tantalum rods were fabricated using type FTaY-1 tantalum powder via the foam impregnation-sintering method. Mechanical testing with the Instron 8801 universal testing machine and finite element analysis (FEA) assessed single tantalum rod implantation and impaction bone grafting combined with rod implantation. A total of 86 osteonecrosis of the femoral head (ONFH) patients (94 hips) were treated: the experimental group (45 patients, 50 hips) underwent surgical hip dislocation (SHD) with impaction bone grafting and tantalum rod implantation, while the control group (41 patients, 44 hips) received single rod implantation. Primary failure criteria included femoral head collapse (≥ 2 mm) or total hip arthroplasty. Patient-reported outcomes (PROs), including Harris Hip Score (HHS), Visual Analog Score (VAS), Hip Outcome Score Activities of Daily Living Subscale (HOS-ADL), and Hip Outcome Score Sport-Specific Subscale (HOS-SSS), were analyzed based on Minimum Clinically Important Difference (MCID). Results FEA confirmed stresses below the material’s yield and compressive strength. At 3 years, survival rates for ARCO (Association Research Circulation Osseous) stage IIb and IIc were higher in the experimental group (100%, 80.38%) than the control group, while stage IIa survival was 100% in the control group. The experimental group also had higher MCID attainment for HHS, HOS-ADL, and HOS-SSS. Conclusions Compared with single TaBw01 implantation, impaction bone grafting combined with TaBw01 implantation via SHD demonstrated superior outcomes for ARCO stage IIb and IIc, with a minimum 2-year follow-up. while single TaBw01 implantation may be more suitable for stage IIa. This study emphasizes the importance of combining biological and biomechanical reconstruction in ONFH treatment.